Forced Labor Trafficking and Human Security From Various Perspective - Norliza Dolhan; Zarina Othman; Nor Azizan Idris (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2020)
Today's industrial revolution provides much of the facility to universal humanity. However, the current trend of modern technology has also witnessed non-traditional and cross-border threats such as drugs and fire arms smuggling and also heinous crime notably forced labor trafficking. This study addresses issues of forced labor trafficking from various perspectives across the world and their impact on the human security. The concept of human security is used in this study while the approach is qualitative. It includes literary discussions such as books, journals, theses/ dissertations and monographs related to the research topic of this paper. The preliminary findings show that an important factor influencing the trafficking activities of foreign workers is that of recruitment by recruiters in their home countries although they are often associated with exploitation in destination countries. The roles of foreign labor as one of the driving forces of the country's economy and development should be balanced through the human security approach within the policies of foreign workers as these measures are more realistic and relevant.